Automatic three-dimensional geometry and mesh generation of periodic representative volume elements for matrix-inclusion composites. (September 2016) - Schneider, Konrad; Klusemann, Benjamin; Bargmann, Swantje
Highlights: Generation of randomized periodic representative volume elements (RVE) is presented. We introduce a novel method of discretizing the geometry with a periodic mesh topology. The meshing approach is efficient, robust and results in a high quality mesh. RVEs with high number of anisotropic inclusions are achievable. Our new meshing method results in low number of elements still maintaining a high quality mesh. Abstract: This paper introduces an efficient method to automatically generate and mesh a periodic three-dimensional microstructure for matrix-inclusion composites. Such models are of major importance in the field of computational micromechanics for homogenization purposes utilizing unit cell models. The main focus of this contribution is on the creation of cubic representative volume elements (RVEs) featuring a periodic geometry and a periodic mesh topology suitable for the application of periodic boundary conditions in the framework of finite element simulations. Our method systematically combines various meshing tools in an extremely efficient and robust algorithm. The RVE generation itself follows a straightforward random sequential absorption approach resulting in a randomized periodic microstructure. Special emphasis is placed on the discretization procedure to maintain a high quality mesh with as few elements as possible, thus, manageable for computer simulations applicable to high volume concentrations, high number of inclusions and complex inclusion geometries. Examples elucidate the ability of the proposed approach to efficiently generate large RVEs with a high number of anisotropic inclusions incorporating extreme aspect ratios but still maintaining a high quality mesh and a low number of elements.